Physical activity, physical fitness, functional capacity and cognitive performance in older adults: effects of interactive video gaming - Ramnath, Udhir (Department of Human Biology, 2023)
The ageing process is inevitable and is associated with a progressive decline in physical fitness, functional ability as well as cognitive performance due to the deterioration of the various biological, neuro-physiological and social systems. This may lead to an increased vulnerability for age-related diseases and a dependent lifestyle. In addition to the ageing process, sedentary behaviour is a contributing factor that can lead to decreased functional independence. The decline in physical, functional and cognitive performance with age, along with the increased possibility of becoming sedentary as one gets older may highlight the importance of participating in physical activity to acquire health and wellness benefits as well as to maintain independence. The health and wellness benefits of physical activity have been widely studied within the ageing population. Physical activity can be defined as any bodily movement produced by skeletal muscles that will lead to an increase in resting energy expenditure. According to the World Health Organization guidelines on physical activity, adults should accumulate at least 150 minutes of moderate levels of physical activity or at least 75 minutes of vigorous levels of physical activity throughout the week or an equal combination of both levels. Much of the existing research to date has utilized more conventional physical activity interventions, including the use of various training components such as cardiorespiratory, motor coordination, agility, flexibility, balance and strength. These interventions have been shown to improve physical and cognitive parameters in older adults. In recent times, alternative forms of physical activity interventions such as Tai Chi, Yoga, and Interactive Video Games (IVG) have become increasingly popular among older adults. However, there is limited research on the effectiveness of IVG interventions in older adults, particularly for those with memory complaints. IVG involves combining physical activity and exercise with video game play. It allows the individual to control the “avatar” on screen by using various body movements (e.g. if the individual moves to the right, the onscreen character will also move to the right). This provides an opportunity for individuals to increase their energy expenditure by actively participating in these video games. In addition to increasing energy expenditure, IVG incorporates cognitive skills such as executive function, visuospatial skills, attention, working memory and coordination (hand and eye / foot and eye). Recent review articles have identified that a combination of physical and cognitive training intervention's show greater effects on cognitive performance than single-domain physical and cognitive training and subsequently applied physical and cognitive training. IVG has been shown to intensify the effects of physical exercise by controlling neuroplastic changes via additional cognitive exercise. These neuroplastic changes identified after participation in IVG are referred to as improvements in a specialized neural network and a lower dependency on compensational support. Therefore, IVG combines physical skills and abilities with cognitive skills, creating a cognitively stimulating type of physical activity, which may be different to more conventional physical activity. While these positive neuroplastic changes have been identified in some research studies, the underlying neurophysiological mechanism of IVG on cognitive performance and brain function is still poorly understood. Although some research studies have been conducted showing the potential benefits of IVG on physical function and cognitive performance in different population groups over various time frames, not many studies have investigated whether IVG can improve cognitive function in older persons with memory complaints. In addition, to our knowledge, no other studies have compared IVG to conventional multimodal supervised standing and seated exercise in individuals with memory complaints. Therefore, the aim of this thesis was to determine the effects of a 12-week IVG intervention using the X-Box 360 gaming console with Kinect Sports and Adventures games on cognitive performance in older adults, and specifically, in South African older adults, some with memory complaints. The IVG intervention was compared to a conventional multimodal supervised exercise intervention. We hypothesized that the IVG intervention would show greater improvements in measures of cognitive performance and functional ability than the conventional multimodal exercise intervention. The results showed a significant relationship between the number of the correct responses on the Modified Stroop task and scores on the 6-Item Cognitive Impairment test (r=-0.52, p< 0.001) and Grip Strength (r=0.42, p< 0.01). In addition, a significant inverse association was found between incorrect responses on the Modified Stroop task and Functional Reach (r=-0.45, p< 0.01). The final multivariate regression model included age, Functional Reach and right arm Grip Strength, and described 28% of the variance in performance of the Modified Stroop task. In summary, the study illustrated that measures of physical function were related to cognitive performance in high functioning independent living South African older adults. The extent to which a physical exercise intervention can improve these physical function parameters and its effects on cognitive performance warranted further research within South African older adults. Study 2: The aim of the second study was to explore the feasibility of IVG in South African, normal functioning, healthy older adults. We hypothesized that those individuals with lower functional and cognitive performance would perceive the IVG as more difficult. Twenty normal functioning, healthy community-dwelling older adults with a mean age of 70.5 ±5.5 years were invited to participate in the study. Functional ability was assessed using the Dynamic Balance, ‘Timed Up and Go', Functional Reach and Grip Strength tests while cognitive ability was assessed using the Modified Stroop task. Participants played in an IVG session using the X-Box Kinect Adventures software package which comprised of 5 games, including: 20000 leaks, River Rush, Rally Ball, Reflex Ridge and Halo Popper. Heart rate was recorded throughout the session to measure the intensity while playing the game. An interviewer-administered questionnaire was completed after the IVG session, in which participants reported on their levels of enjoyment and the perceived difficulty of each game during the gaming session, using a Likert scale. The mean resting heart rate for the gaming session was 73.4bpm ±12.6. Rally Ball produced the highest average heart rate of 88.0bpm ±14.4 with 20000 Leaks producing the lowest average heart rate of 82.6bpm ±12.3. The average heart rate response for all games was between 55.2% and 58.7% of age-predicted maximum heart rate, suggesting IVG equates to moderate intensity physical activity according to the American College of Sports Medicine criteria. Non-dominant handgrip strength (kg) was inversely associated with the perceived level of difficulty, (High perceived level of difficulty = 19.5kg; Moderate perceived level of difficulty = 27.0kg; Low perceived level of difficulty = 29.1kg; p=0.034). There were significant relationships between some components of functional ability and cognitive performance with the perceived difficulty of the gaming session. Individuals that perceived the game as more difficult had significantly lower cognitive performance scores than those reporting moderate and low levels of difficulty. Most (95%) participants reported that they were interested in participating in IVG in the future. They perceived the games as fun and enjoyable, as a form of stress reduction and a means to improve physical well-being. In addition, our results indicate that older adults enjoyed the IVG and showed interest in participating regularly. In summary, the study showed that IVG was an enjoyable activity for older adults and associated with functional and physical well-being. Future research is needed to determine if IVG can result in improved health, functional ability and cognitive performance in older adults. Study 3: Therefore, the aim of the third study was to measure the effects of a 12- week IVG intervention, using the X-Box 360 Kinect gaming console on cognitive performance and functional ability in healthy older adults, without any known diagnosis of cognitive impairment. A total of 41 healthy participants with a mean age of 72.7 ±6.6 years were recruited from 4 different retirement homes and clusterrandomized into either the IVG group (n=21) or the Cognitively Stimulating Table Games group (n=20). The IVG group participated in moderate intensity X-Box Kinect Adventure games twice a week for one hour while the comparison group participated in Cognitively Stimulating Table games (Board and Card games) for the same duration. Both groups had high attendance rates with all participants completing all 24 of their respective sessions. Baseline physical activity level was assessed using the Yale Physical Activity Survey. Pre-post measures included the 6-Minute Walk test, Dynamic Balance, Timed Up and Go, Grip Strength, Functional Reach, 6-Item Cognitive Impairment test and the Modified Stroop task. Most participants' highest level of education was at primary school level and the most frequent medical condition was hypertension in both groups. More than half of the participants were prescribed medication for various chronic diseases. Functional Reach was the only significant improvement post intervention in favour of the IVG group (p=0.049). The comparison group's average reaction time for all correct responses improved significantly on the Modified Stroop task post intervention compared to the intervention group. After the variables were log transformed, the comparison group showed significant improvement in average reaction time for all correct responses on the Modified Stroop task (p=0.028). The IVG group showed a significant improvement in balance, measured by the Functional Reach test. Cognitively Stimulating Table Games showed significant improvements in reaction time measures of the Modified Stroop task illustrating benefits of such games on improving cognitive performance. In summary, functional ability and cognitive performance improved for most outcomes in both groups, however, many changes were not statistically significant. Therefore, IVG as an intervention program could serve to preserve cognitive and physical function, especially in high functioning, healthy older adults. The results of the first three studies (chapters 2, 3 and 4) showed that physical function was related to cognitive performance in high functioning, independently living older adults. IVG was identified as a fun and enjoyable activity, a means to improve physical health and it equated to moderate intensity physical activity. Furthermore, a 12-week IVG intervention using the X-Box 360 Kinect gaming console and Kinect Adventures games significantly improved balance in healthy older adults when compared to Cognitively Stimulating Table Games. Cognitively Stimulating Table Games significantly improved executive function measured by the Modified Stroop task post intervention. We also found that most functional ability and cognitive performance outcomes improved after 12-weeks of IVG however, many did not reach a level of significance in our cognitively healthy older adult participants. In South Africa, the prevalence of diagnosed MCI is 27% while research on the prevalence of subjective memory complaints is scares. Previous research from systematic reviews and meta-analysis has shown positive effects of physical activity and exercise on cognitive performance in older adults with MCI and memory complaints. This led us to my fourth study, which aimed to examine the efficacy of IVG in older adults with self-reported and objectively determined memory complaints. A few studies have investigated whether active gaming can improve cognitive performance in older adults with subjective memory complaints, however, to our knowledge; no study has been conducted comparing the benefits of IVG to conventional multimodal supervised exercise in older adults with memory complaints. Study 4: The aim of the fourth study was to determine the effects of a 12-week IVG intervention, using the X-Box 360 gaming console with Kinect Sports games, on cognitive performance in South African older adults with subjective and objectively determined memory complaints. This intervention was compared to a conventional multimodal supervised exercise program that served as the comparison group. We hypothesized that the individuals in the intervention group would show greater improvements in measures of cognitive function and functional ability than the comparison group. Forty-five participants with a mean age of 72.4 ±5.4 years were recruited and screened from 6 retirement homes and cluster-randomized into the IVG group (n=23) or the Conventional Multimodal Supervised Exercise (CM; n=22) group. All participants from both groups completed all 24 of their respective exercise sessions. An interviewer-administered questionnaire was conducted to determine demographic, health and physical activity levels at baseline for each participant. Prepost measurements for physical function included the 6-Minute Walk test, Dynamic Balance, Timed Up and Go and Functional Reach. Cognitive performance was measured by the Mini-Mental State Examination (global cognitive function), N-Back task (working memory) and the Modified Stroop task (executive function). The IVG group demonstrated significant improvements in the total number correct responses on the Modified Stroop task (p=0.028) and for average reaction time of correct colour-words (p=0.024), compared to the CM group. Furthermore, the IVG group showed significant improvements in global cognitive function (p=0.005) measured by the Mini-Mental State Examination (MMSE) when compared to the CM group. Functional ability improved significantly in the IVG group, including the 6-Minute walk (p=0.017), Dynamic Balance (p=0.03), Timed Up and Go (p< 0.001) and Functional Reach (p< 0.001). We concluded that the IVG intervention was more effective than 36 Conventional Multimodal Supervised exercise in improving executive and global cognitive performance and functional capacity in older adults with subjective memory complaints. In summary, measures of physical function which included functional reach, grip strength and dynamic balance were associated with cognitive performance in high functioning older adults. Furthermore, older adults enjoyed participating in IVG as a form of physical activity which was also associated with physical well-being. The feasibility and acceptability of the IVG among older adults prompted the study comparing IVG to table games over a 12-week period in healthy older adults. Both, the IVG intervention and table games were effective in improving functional and cognitive measures in healthy older adults but did not reach a level of statistical significance. Therefore, we conducted a similar study using IVG in older adults with subjective and objectively determined memory complaints to determine its effectiveness on cognitive performance and functional ability. In conclusion, IVG was more effective than conventional multimodal supervised exercise in improving measures of cognitive performance and functional ability in older persons with memory complaints. IVG is recommended to help preserve and maintain quality of life and independent living in healthy older adults residing in low-to-middle income countries such as South Africa while greater cognitive and functional benefits may be achieved in those with some level of memory complaints.